Develop design interior spaces for children's theater halls in Baghdad: إخلاص عبد سلمان (Al-Academy, 2016)
The research is marked by (Development Design Interior spaces for children's theater halls in the city of Baghdad). Which consists of four chapters, namely, the first chapter the research problem and the need for him, which included identifying the research problem and of poor achievement of aesthetic values and functional at the scene of the child and its significance in that it is a way of cultural entertainment education of the child and its objectives as it aims to evelop interiors for children's theater, and its limits. Theater Magic Lantern in the city of Baghdad, the second chapter addressed the theoretical framework, which consists of the psychology of the child, and space Children's Theatre and types, forms of children's theater, organize seating (seats) in the space of hall audience in the theater of the child, the extent of vision, sound, security requirements, and the Chapter III include research methodology and analysis of the sample where the descriptive approach adopted in the analysis of the research community and appointed by either the fourth quarter represents a set of results was the most prominent weakness of the aesthetic and functional element in the hall of children's theater with the recommendations and proposals